2022
DOI: 10.5935/1806-6690.20220006
|View full text |Cite
|
Sign up to set email alerts
|

The use of computer vision to classify Xaraés grass according to nutritional status in nitrogen

Abstract: This study is based on the principle that vegetation indexes (VIs), derived from the RGB color model obtained from digital images, can be used to characterize spectral signatures and classify Brachiaria brizantha cv. Xaraés according to nitrogen status (N). From colorimetric data obtained from leaf blade images acquired in the fi eld, three artifi cial neural networks were evaluated according to the performance in the classifi cation of N status: Feedforward Backpropagation (FFBP), Cascade Forward Backpropagat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…In this scenario, a shifting between the contribution of litter and external sources, such as excreta and fertilizers, for supplying nutrients to plants is of higher relevance [17], and N fertilization will probably be required at greater amounts compared with the initial regrowth cycles (Figure 2, in "B" and "C"). Both [21], in Mavuno grass, and [80], in Xaraés palisadegrass, reported that during the intermediate regrowth cycles of the growing season, using the equivalent to 30 kg N ha −1 after each regrowth cycle was enough for the pastures to attain N sufficiency indexes and sustain maximum growth rates. Moreover, [81] observed that tillers that sustain higher pasture growth rates during the beginning of the autumn in stockpiled Marandu palisadegrass correspond to the tillers generations that appeared during the summer season (between January and February), highlighting the importance of an adequate N supply at these periods of the year.…”
Section: Moving To a New Approach On N Fertilization For Tropical Per...mentioning
confidence: 99%
“…In this scenario, a shifting between the contribution of litter and external sources, such as excreta and fertilizers, for supplying nutrients to plants is of higher relevance [17], and N fertilization will probably be required at greater amounts compared with the initial regrowth cycles (Figure 2, in "B" and "C"). Both [21], in Mavuno grass, and [80], in Xaraés palisadegrass, reported that during the intermediate regrowth cycles of the growing season, using the equivalent to 30 kg N ha −1 after each regrowth cycle was enough for the pastures to attain N sufficiency indexes and sustain maximum growth rates. Moreover, [81] observed that tillers that sustain higher pasture growth rates during the beginning of the autumn in stockpiled Marandu palisadegrass correspond to the tillers generations that appeared during the summer season (between January and February), highlighting the importance of an adequate N supply at these periods of the year.…”
Section: Moving To a New Approach On N Fertilization For Tropical Per...mentioning
confidence: 99%
“…Spectral indices obtained from digital images have been used with recognized success in the evaluation of biophysical parameters of different crops. In forage crops, the use of digital images has enabled the instantaneous, nondestructive quantification of leaf area and leaf weight (HUACCHA-CASTILLO et al, 2023), nitrogen fertilization estimation (MANCIN et al, 2022), aboveground biomass estimation (MAIMAITIJIANG et al, 2019), productivity estimation (SERRET et al, 2020), and chlorophyll monitoring (KŘÍŽOVÁ et al, 2022).…”
Section: Introductionmentioning
confidence: 99%